One-punch man. 17, Because I'm the bald cape? - ONE, 1986- (Shonen Jump manga., 2019)
"The hero hunter is near death when the Monster Association attempts to steal him away, unleashing Centichoro in the process. Bang and company face it head-on before Genos boldly enters the fray!"-- <U+01C2>c Back cover.